Thermo-Physical Properties of Metal Oxides Composite Nanolubricants - Nurul Nadia, Mohd Zawawi; W. H., Azmi; A. A. M., Redhwan; M. Z., Sharif (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malaysia., 2018)
Thermal conductivity and viscosity of the different combination of composite nanolubricants for 0.02% volume concentrations at a temperature range of 30 to 80 "C were investigated. AI2O3, SiO2 and TiO2 nanoparticks were dispersed in the Polyalkylene Glycol (PAG 46) lubricant using the two-step method of preparation. Thermal conductivity and viscosity were measured using KD2 Pro Thermal Properties Analyzer and LVDV-lII Rheometer, respectively. The result shows that the thermal conductivity and viscosity of composite nanolubricants decrease with temperature. Composite nanolubricants behaved as Newtonian in the range of the temperatures studied. The most optimum combination of composite nanolubricant is AljOi-SiOjlPAG as it yields higher enhancement in thermal conductivity but lower in viscosity.